1967
DOI: 10.1677/joe.0.0390071
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of Thyrocalcitonin

Abstract: SUMMARY The effect of nephrectomy on the response to thyrocalcitonin was studied in three groups of rats: intact animals on stock diet; parathyroidectomized rats on stock diet; and parathyroidectomized rats on high calcium, low phosphorus diet. In intact rats and in parathyroidectomized rats on a high calcium, low phosphorus diet, nephrectomy did not alter the fall in plasma calcium and phosphate produced by thyrocalcitonin. In parathyroidectomized rats on stock diet, however, plasma calcium wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1968
1968
2015
2015

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…It is possible that the CT-induced fall in plasma phosphate concentration in para¬ thyroidectomized animals is a result of the phosphaturic action of CT, since it has been shown to be abolished by previous nephrectomy (Robinson, Martin, Matthews & Maclntyre, 1967). a-Calcitonin administered to our parathyroidectomized animals, in which we assume bone résorption to be minimal, produced not only a fall in plasma phosphate concentration but also a small fall in plasma calcium concentration.…”
Section: Inorganic Phosphatementioning
confidence: 82%
“…It is possible that the CT-induced fall in plasma phosphate concentration in para¬ thyroidectomized animals is a result of the phosphaturic action of CT, since it has been shown to be abolished by previous nephrectomy (Robinson, Martin, Matthews & Maclntyre, 1967). a-Calcitonin administered to our parathyroidectomized animals, in which we assume bone résorption to be minimal, produced not only a fall in plasma phosphate concentration but also a small fall in plasma calcium concentration.…”
Section: Inorganic Phosphatementioning
confidence: 82%
“…However, it has been clarified that the hormone's hypocalcemic effect is not dependent upon direct inhibition of PTH. This view was well documented by the studies of Tashjian (1965) and Robinson et al (1967) Chase and Aurbach (1970) and Murad et al (1970) found that porcine CT caused small increases (about two-fold) in concen--J6-tration of cyclic AMP in bone and in kidney homogenates in vitro (Murad et al, 1970). These investigators demonstrated that there was little or no effect of dose, whereas PTH showed a log-dose response in this system over a ten to twenty-fold range of cyclic AMP Their studies indicated that pyrophosphate-coated crystals dissolved more slowly.…”
Section: Mechanism Of Actionmentioning
confidence: 55%
“…These effects are due to inhibition of bone resorption as has been shown in many ways in numerous animal experiments [1,5,28,39,44,47,49,57,59].…”
Section: Calcitoninmentioning
confidence: 83%